Neural entrainment to rhythmic speech in children with developmental dyslexia - Power, Alan J.; Mead, Natasha; Barnes, Lisa; Goswami, Usha (Frontiers in Human Neuroscience, 2013)
A rhythmic paradigm based on repetition of the syllable “ba” was used to study auditory, visual and audio-visual oscillatory entrainment to speech in children with and without dyslexia using EEG. Children pressed a button whenever they identified a delay in the isochronous stimulus delivery (500 ms; 2 Hz delta band rate). Response power, strength of entrainment and preferred phase of entrainment in the delta and theta frequency bands were compared between groups. The quality of stimulus representation was also measured using cross-correlation of the stimulus envelope with the neural response. The data showed a significant group difference in the preferred phase of entrainment in the delta band in response to the auditory and audio-visual stimulus streams. A different preferred phase has significant implications for the quality of speech information that is encoded neurally, as it implies enhanced neuronal processing (phase alignment) at less informative temporal points in the incoming signal. Consistent with this possibility, the cross-correlogram analysis revealed superior stimulus representation by the control children, who showed a trend for larger peak r-values and significantly later lags in peak r-values compared to participants with dyslexia. Significant relationships between both peak r-values and peak lags were found with behavioural measures of reading. The data indicate that the auditory temporal reference frame for speech processing is atypical in developmental dyslexia, with low frequency (delta) oscillations entraining to a different phase of the rhythmic syllabic input. This would affect the quality of encoding of speech, and could underlie the cognitive impairments in phonological representation that are the behavioural hallmark of this developmental disorder across languages.